El método de inventario ABC y su influencia en la rentabilidad de almacenes Electro Omega, Ciudad de Orellana, Periodo 2018. - Chicaiza Llangari, Cristian Andrés (2022)
The present research work entitled: THE ABC INVENTORY METHOD AND ITS INFLUENCE ON THE PROFITABILITY OF ELECTRO OMEGA WAREHOUSES, CITY OF ORELLANA, PERIOD 2018, aims to evaluate inventory control and implement the ABC method in the company in order to improve and contribute effectively to the entity's inventory control and improve profitability. The methodology used was the inductive method, the research was cross-sectional and documentary, which allowed obtaining information, analyzing both accounting and bibliographic documentation, the design was non-experimental, the level of exploratory research, its population was of two documentary types and of human Resources. Finally, the ABC inventory method was applied, the annual sales of 2018 were taken and the products that require continuous review were categorized into Type A, a stricter control because it is where the greatest investment is concentrated, Type B the items that requires less control, Type C articles these should have a simple control, then profitability indicators were applied and a final report was made.